Robotics and Mathematics Knowledge in initial teacher education in Supervised Internships - Carneiro, Henrique Gabriel Silva; Souza Junior, Arlindo Jose (Educação Matemática Debate, 2023)
In this study, adapting the Technological and Pedagogical Content Knowledge (TPACK) model, we explored the development of Knowledge in Robotics and Mathematics (CRM) in six trainees of an undergraduate degree program in Mathematics at a Brazilian federal university, using a qualitative approach. Our objective was to understand how CRM develops in the initial training, during the Pre-Professional Internship, by exploring Educational Robotics in the teaching and learning of Mathematics. The study shows that, through the tasks developed on the Open Roberta platform, the future teachers developed Knowledge in Robotics and Mathematics by working with mathematical and robotics concepts through programming.